Preparation process of secondary bonded lithium tantalate composite substrate and flexible lithium tantalate composite substrate

CN122294825BActive Publication Date: 2026-10-09DABO TECHNOLOGY (SHANGHAI) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610669991.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-15
Publication Date
2026-10-09
Estimated Expiration
2046-05-15

AI Technical Summary

Technical Problem

然而受限于钽酸锂晶圆自身的机械性能,目前仍常用线切割和激光切割方式为主,此两种方式在制备超薄钽酸锂晶圆时会导致材料内部应力集中,从而引发微裂纹扩展,因此这两种方式切割得到超薄钽酸锂晶圆的碎片率较高,使得成品率不足10%,难以稳定获得完整、无缺陷的柔性超薄钽酸锂晶圆

Benefits of technology

1.根据本申请的二次键合钽酸锂复合衬底的制备工艺,获得异质薄膜键合衬底的同时能够解决超薄钽酸锂薄片易碎、难加工、键合不稳定等问题,实现柔性钽酸锂复合衬底的高效、稳定制备,满足工业化生产及前沿产业需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122294825B_ABST
    Figure CN122294825B_ABST
Patent Text Reader

Abstract

The application discloses a preparation process of a secondary bonded lithium tantalate composite substrate and a flexible lithium tantalate composite substrate, and belongs to the technical field of flexible ultrathin lithium tantalate wafer preparation. The preparation process comprises the following steps: (1) ion implantation is performed on a lithium tantalate wafer, and a substrate wafer is subjected to pre-annealing treatment; (2) the implanted surface of the lithium tantalate wafer and the substrate wafer are activated and bonded to obtain a first bonding body, and the lithium tantalate wafer of the first bonding body is thinned to a thickness of 2-50 microns; (3) the lithium tantalate wafer of the first bonding body is secondarily bonded to a flexible substrate to obtain a second bonding body; and (4) the second bonding body is subjected to annealing and peeling to obtain a flexible lithium tantalate composite substrate and a hetero thin film bonding substrate. The method realizes permanent bonding of the ultrathin lithium tantalate wafer and the flexible substrate through two-step bonding, and realizes the conversion of the lithium tantalate wafer from a "fragile sheet" to a flexible lithium tantalate composite substrate which is practical, integrable and flexible.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a fabrication process for a secondary-bonded lithium tantalate composite substrate and a flexible lithium tantalate composite substrate, belonging to the field of flexible ultrathin lithium tantalate wafer fabrication technology. Background Technology

[0002] Lithium tantalate piezoelectric wafers, as a key functional material, are widely used in high-frequency filters, surface acoustic wave devices, optical modulators and sensors due to their advantages such as high Curie temperature, low dielectric loss, excellent piezoelectric response and good chemical stability. They are one of the core basic materials for cutting-edge technology industries such as 5G communication and the Internet of Things.

[0003] With the increasing market demand for flexible electronic products, lithium tantalate materials are required to become thinner and more flexible, in order to prepare flexible lithium tantalate composite substrates with controllable thickness and stable performance. However, due to the inherent mechanical properties of lithium tantalate wafers, wire cutting and laser cutting are still the most commonly used methods. These two methods can lead to stress concentration within the material when preparing ultra-thin lithium tantalate wafers, which can cause microcrack propagation. Therefore, the fragmentation rate of ultra-thin lithium tantalate wafers obtained by these two methods is relatively high, resulting in a yield of less than 10%, making it difficult to consistently obtain complete and defect-free flexible ultra-thin lithium tantalate wafers.

[0004] Meanwhile, due to their thinness and brittle nature, ultrathin lithium tantalate wafers lack effective mechanical support. Therefore, even if ultrathin lithium tantalate wafers are obtained, they cannot be directly subjected to subsequent processing operations such as clamping, cleaning, photolithography deposition, and bending, severely limiting their application and promotion in the field of flexible devices. Therefore, there is an urgent need for a flexible lithium tantalate composite substrate that can be clamped, cleaned, photolithographically deposited, and fully formed. Summary of the Invention

[0005] To address the aforementioned issues, a fabrication process for a two-step bonded lithium tantalate composite substrate is provided. This process first obtains an ultrathin lithium tantalate wafer with a thickness of 2-50 μm through a one-step bonding process, and then achieves permanent bonding between the ultrathin lithium tantalate wafer and a flexible substrate through a two-step bonding process. This truly transforms the lithium tantalate wafer from a "fragile thin sheet" into a flexible lithium tantalate composite substrate that is practical, integrable, and suitable for flexible devices.

[0006] This application provides a fabrication process for a secondary-bonded lithium tantalate composite substrate, comprising the following steps: (1) Ion implantation was performed on the lithium tantalate wafer, with a minimum implantation dose of 4.0 × 10⁻⁶. 16 ions / cm 2 The implantation dose at the edge of the lithium tantalate wafer is greater than the implantation dose at its center, and the substrate wafer is pre-annealed at a temperature not exceeding 500°C. (2) The injection surface of the lithium tantalate wafer and the substrate wafer are activated and bonded to obtain a first bond, and the lithium tantalate wafer of the first bond is thinned to a thickness of 2-50 μm; (3) Polish and clean the lithium tantalate wafer of the first bond body after thinning in step (2), and then perform secondary bonding with the flexible substrate to obtain the second bond body; (4) Anneal the second bonded body and peel it off to obtain a flexible lithium tantalate composite substrate and a heterogeneous thin film bonded substrate.

[0007] Based on the existing lithium tantalum composite substrate, this application can simultaneously obtain a heterogeneous thin film bonded substrate and a flexible lithium tantalum composite substrate by thinning the first bond and secondary bonding it with a flexible substrate. Thus, two different composite substrates can be obtained in one process, improving the utilization rate of lithium tantalum wafers and facilitating industrial promotion.

[0008] By performing regional ion implantation with different dosages in step (1), a uniform ion implantation layer can be formed in the lithium tantalate wafer, which facilitates gradual peeling of the thickness from the outside to the inside. The thinning operation in step (2) yields lithium tantalate single crystal wafers with a thickness of 2–50 μm, laying the foundation for the subsequent preparation of flexible lithium tantalate composite substrates. The secondary bonding in step (3) permanently bonds the lithium tantalate single crystal wafers to the flexible substrate, and the implantation layer of the lithium tantalate wafer is removed by annealing to achieve peeling. The above preparation method can retain the excellent piezoelectric and photoelectric properties of lithium tantalate single crystals, and can also provide mechanical support and buffer for ultrathin lithium tantalate single crystals through flexible substrates, which can eliminate bending stress to suppress warping. This makes the originally hard, brittle, and fragile lithium tantalate single crystal wafers that cannot be operated or processed into flexible, washable, photolithographically coated, and safely bent, so as to obtain a flexible lithium tantalate composite substrate that is practical, integrable, and can be used as a flexible device.

[0009] Optionally, the flexible substrate includes at least one of a polyimide substrate, a polyethylene terephthalate substrate, a polyethylene naphthalate substrate, and an ultrathin metal foil substrate.

[0010] The flexible substrates described above possess good flexibility, strength, and chemical stability, exhibiting high bonding strength with lithium tantalate wafers to achieve permanent bonding. Furthermore, these flexible substrates can impart suitable performance to the composite substrates in specific scenarios. For example, polyimide substrates can improve the performance of flexible lithium tantalate composite substrates at high temperatures, while ultrathin metal foil substrates can be used for conductive flexible devices. Therefore, the types of flexible substrates described above can meet different application requirements and can be customized to specific needs.

[0011] Optionally, the thickness of the flexible substrate is 20-150 μm.

[0012] The thickness of the aforementioned flexible substrate can ensure sufficient substrate support, improve the flexibility of the flexible lithium tantalate composite substrate, and match the thickness of the lithium tantalate wafer, resulting in a composite substrate with better flexibility and structural stability.

[0013] Optionally, the surface roughness of the lithium tantalate wafer of the first bond in step (3) after polishing and cleaning is less than 0.5 nm.

[0014] The aforementioned surface roughness limitation can reduce the impurity content of lithium tantalate wafers and improve surface flatness, thereby increasing the bonding strength between lithium tantalate wafers and flexible substrates, avoiding local peeling or bubbles on the bonding surface of flexible lithium tantalate composite substrates, and thus improving the yield of composite substrates.

[0015] Optionally, step (3) specifically involves thinning the first bonded assembly as follows: S1: The lithium tantalate wafer is thinned to 100-200μm using a 1500#-3000# grinding wheel; and the bond after the first thinning is annealed at 100-200℃ for 4-8 hours. S2: Use a 6500#-8000# grinding wheel for a second thinning process until the lithium tantalate wafer thickness is 50-100μm; S3: Use 12000#-30000# grinding wheels for a third thinning process until the lithium tantalate wafer thickness is 2-50μm.

[0016] The stepwise thinning operation employed in this application ensures rapid removal of excess lithium tantalate wafer layers while avoiding stress concentration during thinning. This reduces surface defects in the thinned lithium tantalate wafer, lowers the breakage rate, and improves the stability and consistency of the fabrication process. The annealing treatment performed after the first thinning step releases stress accumulated during the thinning process, allowing for a significant reduction in the thickness of the thinned lithium tantalate wafer when using higher-mesh grinding wheels. Furthermore, it increases the bonding strength of the flexible lithium tantalate composite substrate, thereby reducing fragmentation and improving yield during subsequent thinning processes.

[0017] Optionally, the annealing temperature in step (4) is 120-230℃, the holding time is 20-75h, and the annealing is divided into three steps of gradient heating.

[0018] The three-step gradient heating annealing method can achieve peeling from the edge inward, thereby improving peeling integrity and reducing defects caused by excessive warpage due to peeling. At the same time, it can also slowly release the bonding stress in the second bond, improving the structural integrity of the composite substrate.

[0019] Optionally, the temperature of the substrate wafer pre-annealing in step (1) is 200-500℃ and the pre-annealing time is 4-72h.

[0020] The aforementioned pre-annealing temperature and time allow for the full release of stress in the substrate wafer, facilitating the improvement of the bonding strength of the first bond and preventing the reintroduction of internal stress or damage to the crystallization of the substrate wafer, thereby obtaining a high-quality flexible lithium tantalate composite substrate.

[0021] Optionally, the specific operation of the three-step gradient heating annealing in step (4) is as follows: S1: First keep warm at 120-150℃ for 5-30 hours; S2: Keep warm at 160-180℃ for 5-30 hours; S3: Finally, keep warm at 180-230℃ for 10-15 hours.

[0022] The temperature and time of the above three-step gradient annealing can create a temperature gradient change, thereby gradually releasing stress from the surface inward and improving the bonding tightness. Furthermore, the temperature and time of the above three-step gradient annealing are also related to the ion implantation concentration of the lithium tantalate wafer. At this temperature, gradual peeling can be achieved to obtain a non-destructive flexible lithium tantalate composite substrate, while also avoiding the introduction of thermal stress into the composite substrate and improving the quality of the flexible lithium tantalate composite substrate.

[0023] Optionally, the substrate wafer is made of a material selected from silicon carbide, silicon, silicon nitride, gallium nitride, potassium oxide, diamond, sapphire, or silicon dioxide.

[0024] Preferably, the substrate wafer is made of silicon carbide.

[0025] The material of the aforementioned substrate wafer can provide mechanical support for the thinning of the lithium tantalate wafer, thereby improving the thickness uniformity of the lithium tantalate wafer in the first bond and preventing the lithium tantalate wafer from cracking.

[0026] Optionally, the initial thickness of the lithium tantalate wafer and the substrate wafer is 200μm-1000μm, and the diameter of the lithium tantalate wafer and the substrate wafer is 2 inches-12 inches.

[0027] Currently, the fabrication of heterogeneous bonding substrates based on lithium tantalate typically involves first ion implantation into a lithium tantalate wafer to obtain a lithium tantalate wafer containing a thin film layer, an implanted layer, and a residual layer. The thin film layer is then bonded to the substrate wafer. Afterward, heating and annealing are performed to vaporize the implanted layer ions, achieving the separation of the thin film layer and the residual layer, resulting in a heterogeneous bonding substrate and a lithium tantalate wafer with the residual layer. However, the thickness of the lithium tantalate wafer with the residual layer obtained under this method is still relatively thick; it is not an ultra-thin lithium tantalate wafer. Therefore, it cannot be reused to bond with a flexible substrate to obtain a flexible lithium tantalate composite substrate. Furthermore, the separation process can cause cracks in the lithium tantalate wafer with the residual layer, and in severe cases, breakage. Therefore, the separated lithium tantalate wafers are usually unusable and are treated as waste.

[0028] In this study, it was found that the residual lithium niobate layer is relatively thick. If a thinning process is used to reduce the thickness, it will be more prone to breakage during peeling, making it difficult to obtain an ultra-thin and damage-free lithium tantalate piezoelectric wafer. Furthermore, it cannot be used for bonding with a flexible substrate. Therefore, without improvement, it is also impossible to prepare an ultra-thin and damage-free lithium tantalate piezoelectric wafer and obtain a flexible lithium tantalate composite substrate through the lithium tantalate piezoelectric wafer. Based on this discovery, it is currently believed that there are two reasons for the breakage of the thinned residual lithium niobate layer. First, there is internal stress in the substrate wafer, which is released during the high-temperature peeling process, thus causing the ultrathin lithium niobate piezoelectric single crystal to form fragments or cracks during the peeling process. Second, because the ion implantation concentration is consistent throughout the implanted layer, the peeling process of the ultrathin lithium niobate piezoelectric wafer (ultrathin residual layer) is a multi-point random peeling process. Therefore, the peeling process will generate additional tension on the ultrathin lithium niobate piezoelectric single crystal, which will also cause the ultrathin lithium niobate piezoelectric wafer to break, affecting the quality. Both of these reasons make it impossible to obtain a flexible lithium tantalate composite substrate by bonding the ultrathin lithium tantalate wafer to the flexible substrate.

[0029] To address the first reason, this application pre-annealing the substrate wafer at temperatures below 500°C to eliminate stress generated during the production or processing of the lithium tantalate wafer, thereby reducing the impact of the substrate wafer on the stripping process and reducing the stripping fragmentation rate. To address the second reason, this application improves the ion implantation of the lithium tantalate wafer by using H ions or H and He ions for gradient ion implantation, so that the implantation dose at the edge of the lithium tantalate wafer is greater than that at its center, resulting in an implantation layer where the ion implantation dose gradually decreases from the outside to the inside. Therefore, stripping from the outside to the inside can be achieved in the annealing process in step (4), reducing the generation of additional stripping pull and further reducing the stripping fragmentation rate.

[0030] Optionally, the ion implantation of the lithium tantalate wafer in the first step can be H ion implantation or H and He ion co-implantation, specifically as follows: S10: Perform one-step H-ion implantation or H and He ion co-implantation on the entire surface of the lithium tantalate wafer, which consists of a central circle, a first outer ring, and a second outer ring from the inside out. When implanting only H ions, the H-ion implantation dose is 4.0 × 10⁻⁶. 16 -7.8×10 16 ions / cm 2 When H and He ions are co-implanted, the H ion implantation dose is 2.0 × 10⁻⁶. 16 -3.9×10 16 ions / cm 2 The He ion implantation dose was 5 × 10⁻⁶. 15 -1×10 16 ions / cm 2 ; S20: Two-step ion implantation is performed on the crystal planes of the first and second outer rings. When implanting H ions alone, the H ion implantation dose is 2 × 10⁻⁶. 16 -2.3×10 16 ions / cm 2 When H and He ions are co-implanted, the H ion implantation dose is 1.0 × 10⁻⁶. 16 -1.2×10 16 ions / cm 2 The He ion implantation dose was 2.5 × 10⁻⁶. 15 -3×10 15 ions / cm 2 , S30: Three-step ion implantation is performed on the crystal plane of the second outer ring. When implanting only H ions, the H ion implantation dose is 2.2 × 10⁻⁶. 16 -3.0×10 16 ions / cm 2 When H and He ions are co-implanted, the H ion implantation dose is 1.1 × 10⁻⁶. 16 -1.5×10 16 ions / cm 2 The He ion implantation dose was 3 × 10⁻⁶. 15 -4×10 15 ions / cm 2 .

[0031] The dosage setting of this ion implantation serves two purposes: first, it enables peeling from the outside in, reducing the fragmentation rate of the ultrathin lithium niobate piezoelectric single crystal wafer and laying the foundation for subsequent bonding with the flexible substrate; second, it ensures the thickness uniformity of the thinned lithium tantalate wafer, improves its bonding strength with the flexible substrate, and thus enhances the various properties of the flexible lithium tantalate composite substrate.

[0032] The aforementioned ion implantation is achieved through three steps to create a partitioned arrangement of ion concentrations on the implantation surface of the lithium tantalate wafer. For the lithium tantalate wafer, H ions or H and He ions are implanted together. After H ions are implanted into the lithium tantalate wafer, a neat weakening layer is formed. When H ions are implanted alone, a heterogeneous thin film substrate with higher film uniformity can be obtained. When H and He ions are implanted together, He ions can be captured by the plateau defects formed by H ions and these plateau defects are expanded and combined with each other through physical action, thereby promoting the peeling of the second bond to obtain a flexible lithium tantalate composite substrate.

[0033] Optionally, the area ratio of the central circle, the first outer ring, and the second outer ring is 1:(1-2.5):(2-4).

[0034] This diameter ratio setting enables uniform peeling from the outside to the inside of the lithium tantalate wafer, while also reducing the warpage of the first bond after peeling, improving its surface flatness, and facilitating bonding with a flexible substrate to obtain a second bond with high bonding strength.

[0035] Optionally, the second step involves activating the H-ion implantation surface of the lithium tantalate wafer and the substrate wafer using plasma activation or surface activation methods.

[0036] According to another aspect of this application, a flexible lithium tantalate composite substrate prepared by the fabrication process of the secondary bonded lithium tantalate composite substrate described in any one of the above claims is provided, characterized in that the thickness of the flexible lithium tantalate composite substrate is 22-200 μm.

[0037] Preferably, the thickness of the flexible lithium tantalate composite substrate is 70-152 μm.

[0038] The beneficial effects of this application include, but are not limited to: 1. The preparation process of the secondary bonded lithium tantalate composite substrate according to this application can solve the problems of fragile, difficult to process and unstable bonding of ultrathin lithium tantalate sheets while obtaining heterogeneous thin film bonded substrates, thereby realizing the efficient and stable preparation of flexible lithium tantalate composite substrates and meeting the needs of industrial production and cutting-edge industries.

[0039] 2. The preparation process of the secondary bonded lithium tantalate composite substrate according to this application yields a flexible lithium tantalate composite substrate that can balance flexibility and structural stability, meeting the requirements of flexible devices for substrate thinning and flexibility, and improving the application prospects of flexible lithium tantalate composite substrates.

[0040] 3. According to the preparation process of the secondary bonded lithium tantalate composite substrate of this application, on the basis of obtaining a heterogeneous thin film bonded substrate, the ultrathin lithium tantalate wafer, the substrate wafer and the flexible substrate are bonded by secondary bonding, which can have stable piezoelectric and photoelectric properties and meet the performance requirements of the flexible lithium tantalate composite substrate.

[0041] 4. According to the preparation process of the secondary bonded lithium tantalate composite substrate of this application, a flexible lithium tantalate composite substrate and a heterogeneous thin film bonded substrate are obtained through secondary bonding. The preparation process is easy to operate and has high repeatability, which greatly saves production costs and facilitates mass production. Attached Figure Description

[0042] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings: Figure 1 This is a schematic diagram of the structure of the lithium tantalate wafer involved in the embodiments and comparative examples of this application.

[0043] Figure 2 This is a flowchart of the composite substrate involved in the embodiments and comparative examples of this application.

[0044] Figure 3 This is a surface view of the flexible lithium tantalate composite substrate prepared in Example 3 of this application.

[0045] Figure 4 This is a surface view of the flexible lithium tantalate composite substrate prepared in Comparative Example 4 of this application.

[0046] 1. Central circle; 2. First outer ring; 3. Second outer ring; 11. Substrate wafer; 12. Lithium tantalate wafer; 13. First bond; 14. Flexible substrate; 15. Second bond; 16. Heterogeneous thin film bonding substrate; 17. Flexible lithium tantalate composite substrate. Detailed Implementation

[0047] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0048] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application were all purchased commercially.

[0049] Unless otherwise specified, the methods used in the embodiments and comparative examples of this application are conventional methods in the prior art.

[0050] Example 1 This embodiment relates to a fabrication process for a secondary-bonded lithium tantalate composite substrate, comprising the following steps: (1) Reference Figure 1-2H ion implantation was performed on lithium tantalate wafer 12, with the implantation dose at the edge of the lithium tantalate wafer 12 being greater than that at the center. The Si substrate wafer 11 was then pre-annealed at 200°C for 72 hours. The specific procedure for H-ion implantation on lithium tantalate wafer 12 is as follows: S10: Reference Figure 1 A one-step H-ion implantation was performed on the entire surface of lithium tantalate wafer 12, which consists of a central circle 1, a first outer ring 2, and a second outer ring 3 from the inside out. The implantation dose was 4.0 × 10⁻⁶. 16 ions / cm 2 ; S20: Perform two-step H ion implantation on the crystal planes of the first outer ring 2 and the second outer ring 3, with an implantation dose of 2.0 × 10⁻⁶. 16 ions / cm 2 ; S30: Three-step H ion implantation is performed on the crystal plane of the second outer ring 3, with an implantation dose of 2.2 × 10⁻⁶. 16 ions / cm 2 The area ratio of the central circle 1, the first outer ring 2, and the second outer ring 3 is 1:1:2. (2) The H-ion implantation surface of the lithium tantalate wafer 12 and the Si substrate wafer 11 are surface activated and bonded to obtain the first bond 13. The lithium tantalate wafer 12 of the first bond 13 is thinned to a thickness of 50 μm. The specific thinning operation is as follows: S1: The first thinning was performed using a 3000# grinding wheel until the thickness of the lithium tantalate wafer 12 was 200μm; and the bond body after the first thinning was annealed at 100℃ for 8 hours. S2: A second thinning process is performed using a 6500# grinding wheel until the thickness of the lithium tantalate wafer 12 is 100μm; S3: A third thinning process was performed using a 12000# grinding wheel until the thickness of the lithium tantalate wafer 12 was 50μm; (3) Polish and clean the lithium tantalate wafer 12 of the first bond body 13 after thinning in step (2) until the surface roughness is less than 0.5 nm, and then perform secondary bonding with a flexible substrate 14 (polyimide substrate) with a thickness of 20 μm to obtain the second bond body 15; (4) The second bond 15 is kept at 150°C for 30 hours, then at 180°C for 30 hours, and finally at 230°C for 15 hours for annealing treatment, and the flexible lithium tantalate composite substrate 17 and the heterogeneous thin film bond substrate 16 are obtained by peeling.

[0051] Example 2 This embodiment relates to a fabrication process for a secondary-bonded lithium tantalate composite substrate, comprising the following steps: (1) Reference Figure 1-2 H ion implantation was performed on the lithium tantalate wafer 12, with the implantation dose at the edge of the lithium tantalate wafer 12 being greater than that at the center, and the Si substrate wafer 11 was pre-annealed at 200°C for 72 hours. The specific procedure for H-ion implantation on lithium tantalate wafer 12 is as follows: S10: Reference Figure 1 A one-step H-ion implantation was performed on the entire surface of lithium tantalate wafer 12, which consists of a central circle 1, a first outer ring 2, and a second outer ring 3 from the inside out. The implantation dose was 7.8 × 10⁻⁶. 16 ions / cm 2 ; S20: Two-step H ion implantation is performed on the crystal planes of the first outer ring 2 and the second outer ring 3, with an implantation dose of 2.3 × 10⁻⁶. 16 ions / cm 2 ; S30: Three-step H ion implantation is performed on the crystal plane of the second outer ring 3, with an implantation dose of 3.0 × 10⁻⁶. 16 ions / cm 2 The area ratio of the central circle 1, the first outer ring 2, and the second outer ring 3 is 1:2.5:4. (2) The H-ion implantation surface of the lithium tantalate wafer 12 and the Si substrate wafer 11 are surface activated and bonded to obtain the first bond 13. The lithium tantalate wafer 12 of the first bond 13 is thinned to a thickness of 2 μm. The specific thinning operation is as follows: S1: The first thinning was performed using a 1500# grinding wheel until the thickness of the lithium tantalate wafer 12 was 100μm; and the bond body after the first thinning was annealed at 200℃ for 4 hours. S2: A second thinning process was performed using an 8000# grinding wheel until the thickness of the lithium tantalate wafer 12 was 50μm; S3: Use a 30000# grinding wheel for a third thinning process until the thickness of the lithium tantalate wafer 12 is 2μm; (3) Polish and clean the lithium tantalate wafer 12 of the first bond body 13 after thinning in step (2) until the surface roughness is less than 0.5 nm, and then perform secondary bonding with a flexible substrate 14 (ultra-thin metal foil substrate) with a thickness of 150 μm to obtain the second bond body 15. Step 4: The second bond 15 is annealed by holding it at 120°C for 5 hours, then at 160°C for 5 hours, and finally at 180°C for 10 hours, and then peeled off to obtain the flexible lithium tantalate composite substrate 17 and the heterogeneous thin film bonded substrate 16.

[0052] Example 3 This embodiment relates to a fabrication process for a secondary-bonded lithium tantalate composite substrate, comprising the following steps: (1) Reference Figure 1-2 H ion implantation was performed on the lithium tantalate wafer 12, with the implantation dose at the edge of the lithium tantalate wafer 12 being greater than that at the center, and the SiC substrate wafer 11 was pre-annealed at 300°C for 12 hours. The specific procedure for H-ion implantation on lithium tantalate wafer 12 is as follows: S10: Reference Figure 1 A one-step H-ion implantation was performed on the entire surface of lithium tantalate wafer 12, which consists of a central circle 1, a first outer ring 2, and a second outer ring 3 from the inside out. The implantation dose was 7.4 × 10⁻⁶. 16 ions / cm 2 ; S20: Perform two-step H ion implantation on the crystal planes of the first outer ring 2 and the second outer ring 3, with an implantation dose of 2.1 × 10⁻⁶. 16 ions / cm 2 ; S30: Three-step H ion implantation is performed on the crystal plane of the second outer ring 3, with an implantation dose of 2.5 × 10⁻⁶. 16 ions / cm 2 The area ratio of the central circle 1, the first outer ring 2, and the second outer ring 3 is 1:2:3. (2) The H-ion implantation surface of the lithium tantalate wafer 12 and the SiC substrate wafer 11 are plasma activated and bonded to obtain the first bond 13. The lithium tantalate wafer 12 of the first bond 13 is thinned to a thickness of 30 μm. The specific thinning operation is as follows: S1: The lithium tantalate wafer 12 was thinned to 120μm using a 3000# grinding wheel; and the bond body after the first thinning was annealed at 150℃ for 6 hours. S2: A second thinning process is performed using an 8000# grinding wheel until the thickness of the lithium tantalate wafer 12 is 80μm; S3: A third thinning process was performed using a 30000# grinding wheel until the thickness of the lithium tantalate wafer 12 was 30μm; (3) Polish and clean the lithium tantalate wafer 12 of the first bond body 13 after thinning in step (2) until the surface roughness is less than 0.5 nm, and then perform secondary bonding with a flexible substrate 14 (polyethylene terephthalate substrate) with a thickness of 60 μm to obtain the second bond body 15. (4) The second bond 15 was annealed by holding it at 150°C for 10 hours, then at 170°C for 10 hours, and finally at 190°C for 10 hours, and the resulting flexible lithium tantalate composite substrate 17 and heterogeneous thin film bonded substrate 16 were obtained by peeling. The surface pattern of the obtained flexible lithium tantalate composite substrate 16 is shown in the figure. Figure 3As shown, its surface quality is good and can meet the needs of industrial use.

[0053] Example 4 The difference between this embodiment and Embodiment 3 is that the thickness of the polyethylene terephthalate substrate is 10 μm.

[0054] Example 5 The difference between this embodiment and embodiment 3 is that in step (3), the lithium tantalate wafer 12 on the surface of the first bond 13 is polished and cleaned until the surface roughness is 0.7 nm.

[0055] Example 6 The difference between this embodiment and Embodiment 3 is that the specific operation of H ion implantation is as follows: S20: Two-step H ion implantation is performed on the crystal planes of the first outer ring 2 and the second outer ring 3, with an implantation dose of 2.4 × 10⁻⁶. 16 ions / cm 2 The rest is the same as in Example 3.

[0056] Example 7 The difference between this embodiment and embodiment 3 is that in step (4), the second bond 15 is annealed once at 190°C for 30 hours, without step annealing, and the rest is the same as in embodiment 3.

[0057] Example 8 The difference between this embodiment and Embodiment 3 is that the specific operation of ion implantation in step (1) is as follows: S10: Perform a one-step H and He ion co-implantation on the entire surface of the lithium tantalate wafer 12, which consists of a central circle, a first outer ring, and a second outer ring from the inside out. The H ion implantation dose is 2.0 × 10⁻⁶. 16 ions / cm 2 The He ion implantation dose was 5 × 10⁻⁶. 15 ions / cm 2 ; S20: Two-step H and He ion implantation is performed on the crystal planes of the first and second outer rings, with an H ion implantation dose of 1.0 × 10⁻⁶. 16 ions / cm 2 The He ion implantation dose was 2.5 × 10⁻⁶. 15 ions / cm 2 ; S30: Three-step ion implantation is performed on the crystal plane of the second outer ring. When H and He ions are implanted together, the H ion implantation dose is 1.1 × 10⁻⁶. 16 ions / cm 2 The He ion implantation dose was 3 × 10⁻⁶. 15 ions / cm 2The rest is the same as in Example 3.

[0058] Example 9 The difference between this embodiment and Embodiment 3 is that the specific operation of ion implantation in step (1) is as follows: S10: Perform a one-step H and He ion co-implantation on the entire surface of the lithium tantalate wafer 12, which consists of a central circle, a first outer ring, and a second outer ring from the inside out. The H ion implantation dose is 3.9 × 10⁻⁶. 16 ions / cm 2 The He ion implantation dose was 1×10⁻⁶. 16 ions / cm 2 ; S20: Two-step H and He ion implantation is performed on the crystal planes of the first and second outer rings, with an H ion implantation dose of 1.2 × 10⁻⁶. 16 ions / cm 2 The He ion implantation dose was 3 × 10⁻⁶. 15 ions / cm 2 ; S30: Three-step ion implantation is performed on the crystal plane of the second outer ring. When H and He ions are implanted together, the H ion implantation dose is 1.5 × 10⁻⁶. 16 ions / cm 2 The He ion implantation dose was 4 × 10⁻⁶. 15 ions / cm 2 The rest is the same as in Example 3.

[0059] Comparative Example 1 The difference between this comparative example and Example 3 is that the SiC substrate wafer is not pre-annealed at 300°C for 12 hours; that is, the SiC substrate wafer is not treated in any way. Otherwise, it is the same as Example 3.

[0060] Comparative Example 2 The difference between this comparative example and Example 3 is that the SiC substrate wafer was pre-annealed at 600°C for 12 hours, while the rest is the same as Example 3.

[0061] Comparative Example 3 The difference between this comparative example and Example 3 is that in the H-ion implantation step S10: the entire surface of the lithium tantalate wafer, consisting of a central circle 1, a first outer ring 2, and a second outer ring 3 arranged sequentially from the inside out, is subjected to one-step H-ion implantation, with an implantation dose of 3.0 × 10⁻⁶. 16 ions / cm 2 The rest is the same as in Example 3.

[0062] Comparative Example 4 The difference between this comparative example and Example 3 is that the specific operation of H ion implantation is as follows: A one-step H-ion implantation was performed on the entire surface of a lithium tantalate wafer, consisting of a central circle 1, a first outer ring 2, and a second outer ring 3, from the inside out. The implantation dose was 7.4 × 10⁻⁶. 16 ions / cm 2 Only one H ion implantation was performed, and the rest was the same as in Example 3. The surface pattern of the resulting flexible lithium tantalate composite substrate is shown in the figure. Figure 4 As shown, its surface quality is poor.

[0063] Test Example 1 Flexible lithium tantalate composite substrates and heterogeneous thin-film bonding substrates were prepared according to the methods described in the above embodiments and comparative examples. 100 substrates were prepared for each embodiment or comparative example. The fragmentation rate of the flexible lithium tantalate composite substrates and the TTV, Warp, and BOW of the flexible lithium tantalate composite substrates were measured. The test results are shown in Table 1. Fragmentation rate = (number of fragments / 100) × 100%.

[0064] Table 1

[0065] Test Example 2 The composite substrates prepared in the above embodiments can all be clamped, and when they are subjected to photolithography, they have good flatness and stability, and the film uniformity and adhesion are good. Therefore, it is proven that the composite substrate of this application has excellent photolithography effect.

[0066] The fragment-free and intact composite substrates prepared in the above embodiments and comparative examples were cleaned using standard RCA cleaning. For each embodiment or comparative example, 100 fragment-free and intact composite substrates were cleaned, and the fragmentation rate after cleaning was statistically analyzed. The test results are shown in Table 2. Fragmentation rate after cleaning = (number of fragments after cleaning / 100) × 100%. Since the flexible lithium tantalum composite substrate of Comparative Example 3 could not be peeled off, Comparative Example 3 could not be tested and is represented by "-".

[0067] Table 2

[0068] The above description is merely an embodiment of this application, and the scope of protection of this application is not limited to these specific embodiments, but is determined by the claims of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the technical concept and principles of this application should be included within the scope of protection of this application.

Claims

1. A fabrication process for a secondary-bonded lithium tantalate composite substrate, characterized in that, Includes the following steps: (1) Ion implantation was performed on the lithium tantalate wafer, with a minimum implantation dose of 4.0 × 10⁻⁶. 16 ions / cm 2 The implantation dose at the edge of the lithium tantalate wafer is greater than the implantation dose at its center, and the substrate wafer is pre-annealed at a temperature not exceeding 500°C. (2) The injection surface of the lithium tantalate wafer and the substrate wafer are activated and bonded to obtain a first bond, and the lithium tantalate wafer of the first bond is thinned to a thickness of 2-50 μm; (3) Polish and clean the lithium tantalate wafer of the first bond body after thinning in step (2), and then perform secondary bonding with the flexible substrate to obtain the second bond body; (4) Anneal the second bonded body and peel it off to obtain a flexible lithium tantalate composite substrate and a heterogeneous thin film bonded substrate; In step (1), the lithium tantalate wafer is ion implanted with H ions or with both H and He ions. The specific operation is as follows: S10: Perform one-step H-ion implantation or H and He ion co-implantation on the entire surface of the lithium tantalate wafer, which consists of a central circle, a first outer ring, and a second outer ring from the inside out. When implanting only H-ions, the H-ion implantation dose is 4.0 × 10⁻⁶. 16 -7.8×10 16 ions / cm 2 When H and He ions are co-implanted, the H ion implantation dose is 2.0 × 10⁻⁶. 16 -3.9×10 16 ions / cm 2 The He ion implantation dose was 5 × 10⁻⁶. 15 -1×10 16 ions / cm 2 ; S20: Two-step ion implantation is performed on the crystal planes of the first and second outer rings. When implanting H ions alone, the H ion implantation dose is 2 × 10⁻⁶. 16 -2.3×10¹⁶ ions / cm 2 When H and He ions are co-implanted, the H ion implantation dose is 1.0 × 10⁻⁶. 16 -1.2×10 16 ions / cm 2 The He ion implantation dose was 2.5 × 10⁻⁶. 15 -3×10 15 ions / cm 2 ; S30: Three-step ion implantation is performed on the crystal plane of the second outer ring. When implanting only H ions, the H ion implantation dose is 2.2 × 10⁻⁶. 16 -3.0×10 16 ions / cm 2 When H and He ions are co-implanted, the H ion implantation dose is 1.1 × 10⁻⁶. 16 -1.5×10 16 ions / cm 2 The He ion implantation dose was 3 × 10⁻⁶. 15 -4×10 15 ions / cm 2 ; The area ratio of the central circle, the first outer ring, and the second outer ring is 1:(1-2.5):(2-4); Step (2) specifically involves thinning the first bond: S1: The lithium tantalate wafer is thinned to 100-200μm using a 1500#-3000# grinding wheel; and the bond after the first thinning is annealed at 100-200℃ for 4-8 hours. S2: Use a 6500#-8000# grinding wheel for a second thinning process until the lithium tantalate wafer thickness is 50-100μm; S3: Use 12000#-30000# grinding wheels for a third thinning process until the lithium tantalate wafer thickness is 2-50μm; The annealing temperature in step (4) is 120-230℃, the holding time is 20-75h, and it is divided into three steps of gradient heating annealing. The specific operation of the three-step gradient heating annealing in step (4) is as follows: S1: First keep warm at 120-150℃ for 5-30 hours; S2: Keep warm at 160-180℃ for 5-30 hours; S3: Finally, keep warm at 180-230℃ for 10-15 hours; In step (1), the temperature for pre-annealing the substrate wafer is 200-500℃ and the pre-annealing time is 4-72h.

2. The preparation process of the secondary-bonded lithium tantalate composite substrate according to claim 1, characterized in that, The flexible substrate includes at least one of polyimide substrate, polyethylene terephthalate substrate, polyethylene naphthalate substrate, and ultrathin metal foil substrate.

3. The preparation process of the secondary-bonded lithium tantalate composite substrate according to claim 2, characterized in that, The thickness of the flexible substrate is 20-150 μm.

4. The preparation process of the secondary-bonded lithium tantalate composite substrate according to any one of claims 1-3, characterized in that, The surface roughness of the lithium tantalate wafer of the first bond in step (3) after polishing and cleaning is less than 0.5 nm.

5. The preparation process of the secondary-bonded lithium tantalate composite substrate according to claim 1, characterized in that, The substrate wafer is made of a material selected from silicon carbide, silicon, silicon nitride, gallium nitride, potassium oxide, diamond, sapphire, or silicon dioxide.

6. The preparation process of the secondary-bonded lithium tantalate composite substrate according to claim 1, characterized in that, The initial thickness of the lithium tantalate wafer and the substrate wafer is 200μm-1000μm, and the diameter of the lithium tantalate wafer and the substrate wafer is 2 inches-12 inches.

7. The flexible lithium tantalate composite substrate prepared by the fabrication process of the secondary-bonded lithium tantalate composite substrate according to any one of claims 1-6 is characterized in that, The thickness of the flexible lithium tantalate composite substrate is 22-200 μm.

Citation Information

Patent Citations

  • Wafer bonding method and preparation method for foreign substrate

    CN106711027A

  • Composite single crystal piezoelectric substrate film and preparation method thereof

    CN111128699A

  • Thinning method of large-size lithium niobate wafer

    CN120839660A

  • Method for transferring thin film layer material to a flexible substrate using a hydrogen ion splitting technique

    US20040224482A1